Preserving sensory attributes of roasted peanuts using edible coatings. (3rd December 2012) - Riveros, Cecilia G.; Mestrallet, Marta G.; Quiroga, Patricia R.; Nepote, Valeria; Grosso, Nelson R
Summary: Peanut products are susceptible to develop rancid and off‐flavours through lipid oxidation. Preservation of these products is one of the problems in the peanut industry. The purpose of this work was to determine the sensory and chemical stability of roasted peanuts (RP) coated with different edible coatings: carboxymethyl cellulose (RP‐CMC), methyl cellulose (RP‐MC) or whey protein (RP‐WPI) during storage. Sensory attributes and chemical indicators (peroxide and p ‐anisidine values, and conjugated dienes) of lipid oxidation were measured during storage. Chemical indicator values and intensity ratings of oxidised and cardboard flavours had lower increase in RP‐CMC, RP‐MC and RP‐WPI during storage than in RP, whereas roasted peanutty flavour showed a lower decrease. The stability of RP‐CMC is about a double longer with respect to RP. These results indicate that edible coatings preserve the sensory properties of roasted peanuts. Carboxymethyl cellulose exhibited the best protecting effect on this product.